Hubungan Antara Lama Kontak Karyawan Bengkel Cuci Kendaraan Dengan Kejadian Dermatitis Kontak Akibat Kerja Di Kecamatan Banjarsari Kota Surakarta - , Adly; , dr. Nurrachmat Mulianto, M.Sc., Sp.K.K; , dr. Ratih Pramuningtyas, Sp.KK (2015)
Background: Occupational contact dermatitis (OCD) prevalence in the world remains high. Skin contact to the causative agents for a long period can cause skin susceptibility to employees. Vehicle wash station is one of the places that are at risk. Research Purpose: This research aims to know the correlation between contact duration of vehicle wash station employees with the incidence of occupational contact dermatitis at Kecamatan Banjarsari Kota Surakarta. Research method: Research design using analytic observational cross sectional approach. The number of survey respondents were 60 vehicle wash station employees. Sampling technique was using simple random sampling. Primary data were analyzed by Chi Square test using SPSS 21 program. Result: The result showed that p = 0,067 (p < 0,2) which shows that there is a significant correlation between contact duration with the incidence of OCD. Conclusion: there is a significant correlation between contact duration of vehicle wash station employees with the incidence of occupational contact dermatitis at Kecamatan Banjarsari Kota Surakarta.